2015
DOI: 10.1037/bne0000067
|View full text |Cite
|
Sign up to set email alerts
|

Strength and fine dexterity recovery profiles after a primary motor cortex insult and effect of a neuronal cell graft.

Abstract: The aim of this study was to set up (a) a large primary motor cortex (M1) lesion in rodent and (b) the conditions for evaluating a long-lasting motor deficit in order to propose a valid model to test neuronal replacement therapies aimed at improving motor deficit recovery. A mitochondrial toxin, malonate, was injected to induce extensive destruction of the forelimb M1 cortex. Three key motor functions that are usually evaluated following cerebral lesion in the clinic-strength, target reaching, and fine dexteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 61 publications
2
23
1
Order By: Relevance
“…25 Still in the context of neuronal cell culture, it has been shown that oriented scaffolds are able to guide the development of neurites and axons in one preferential direction and can help in a suitable tissue reconstruction. [26][27][28] Thus, for the scaffolding purpose, and also more generally for extending the scope of LMWG applications, our objective was to explore how fluidics (or microfluidics) can drive the self-assembly of the gelator into well-defined structures and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…25 Still in the context of neuronal cell culture, it has been shown that oriented scaffolds are able to guide the development of neurites and axons in one preferential direction and can help in a suitable tissue reconstruction. [26][27][28] Thus, for the scaffolding purpose, and also more generally for extending the scope of LMWG applications, our objective was to explore how fluidics (or microfluidics) can drive the self-assembly of the gelator into well-defined structures and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical lesions focused on the caudal forelimb motor area (M1) were induced by malonate injection (5 μl, 3M solution, pH 7.4 in PBS; Sigma-Aldrich, France) ( n = 53) or PBS for the sham group ( n = 8) [ 27 ] at the following stereotaxic coordinates: 2.5 mm lateral to Bregma, and 2 mm deep. Only animals that displayed substantial neurological dysfunctions (grip strength < 60% of pre-lesion value, n = 46 out of 53 lesioned rats) 1 week after injury were selected (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another group of lesioned animals each received five implants without any cells (Implants Alone group, n = 6), and another group underwent the same surgery but the implants were immediately removed (Sham Implants group, n = 10). The final group of lesioned rats received a cell graft of 5 × 10 5 hNSCs, by perfusion of 5 μl of cell suspension at 1 μl/min (hNSCs group, n = 6), as already described elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations